Barbaric Splendour - Martin, Toby F. (Archaeopress, 2020)
This book comprises a collection of essays comparing late Iron Age and Early Medieval art. Fundamentally, the book asks what making images meant on the fringe of the expanding or contracting Roman empire, particularly as the art from both periods drew heavily from - but radically transformed - imperial imagery.